Consumer acceptance on Halal e-Inspection / Wan Ahmad Sabirin Ali Azizan - Ali Azizan, Wan Ahmad Sabirin (2016)
Halal e-Inspection is a new innovation in Halal certification process that could simplify and enhance the current tedious and time-consuming certification process. Advances in technology have created novel ways of handling daily affairs. As technology advances the certification process will have to adapt to fit current technology changes to be applied on the current manual inspection process. Past studies have shown the common research on the acceptance of e-services and on how they accept or not if Halal e-Inspection being implemented as the new approach in the Halal certification process. To address Halal e-Inspection in the light of the theoretical framework, Extension of Technology acceptance model (ETAM), the current manual Halal inspection current process is leveraged into the online setting. On the basis of an interview with Halal expert, ETAM literatures, the research model is developed to indicate e-Inspection acceptance among targeted respondents namely Halal consumers from Food and Beverages services sector, Halal consumers from Food and Beverages manufacturing sector and Halal consumers from interested parties (e.g. Home Bakers). The model was tested with a survey sample 86. It contains of 17 questions excluding the demographic profile of the desired respondents. The findings of the study indicate that Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment, Amount of Information, Perceived Security, and Trust were the main factors influencing Halal consumers' acceptance on the usage of e-Inspection in the Halal certification process.